Outcome after ileal pouch‐anal anastomosis in ulcerative colitis patients: experience during a 27‐year period. Issue 10 (4th August 2016) - Tonelli, Francesco; Giudici, Francesco; Di Martino, Carmela; Scaringi, Stefano; Ficari, Ferdinando; Addasi, Rami
Abstract : Background: No previous study describes the postoperative outcome and functional results after ileal pouch‐anal anastomosis (IPAA), performed in ulcerative colitis by the same surgical team with the different anastomotic techniques adopted in a 27‐year period. Methods: Prospectively, consecutive 333 ulcerative colitis patients operated adopting different IPAA techniques during the open surgery period 1984–2011 were enrolled. IPAA was performed using single stapling (SS) technique in 38 patients, double stapling (DS) technique in 235 patients (TIA stapler 42 patients, Endo‐GIA 131 patients, Contour 62 patients) and handsewn IPAA in 60 patients. Results: Statistically different early and late complications were recorded among the different IPAA techniques. A lower frequency of daily and nocturnal defecations and a higher level of continence were observed in the DS‐IPAA compared to handsewn IPAA. The distance between the anastomotic line and the anal verge was significantly lower in DS Endo‐GIA or DS Contour groups than in the DS TIA and SS. In SS IPAA group, 31.6% developed cuffitis compared to 14.4% belonging to DS group, at a mean follow‐up of 140.4 months. Conclusions: Technical improvements changed the IPAA technique. Stapled IPAA is characterized by better functional outcome than handsewn IPAA. DS Endo‐GIA and Contour IPAA are followed by lower risk of cuffitis.